Acute and subacute toxicity study of the methanolic extract of olea europea.L leaves in Wistar rat - Hinad Ibrahim (EDP Sciences, 2021)
Olea europea.L (olive tree) is a plant widely used in the world. Its leaves have an extensive use in traditional herbal medicine to prevent and/or treat several diseases especially in Mediterranean regions. Despite this, research into the study of its toxicity is very limited in the literature. For this, this study aims to study the acute and subacute toxicity of methanolic extract olive leaves in Wistar rats. To study acute toxicity, four dose levels (50,300,2000 and 5000 mg/kg body weight) were tested by single oral administration to Wistar rats. The subacute toxicity for 28 days was conducted by daily oral administration of methanolic extract of olive leaves at doses 1000,2000 and 3000 mg/kg in rats Wistar. After fourteen days of the administration of escalating doses, no deaths were recorded in the animals and no clinically detectable signs were observed. The results of subacute toxicity showed that the body weight of rats was not significantly changed by administration of methanolic extract of olive leaves. Monitoring of the behavior of the rats during the study showed the appearance of some manifestations of tremor, agitation and diarrhea in rats treated with the dose of 3000mg/kg. Grosse examination of the kidneys and liver revealed no changes in those organs and histopathological examination showed congestion and inflammation of the fat in rats treated with the dose of 3000mg/kg. the hematological profile showed no significant changes of the measured hematological parameters. Olive leaves should be used with care and caution since its methanolic extract caused some signs of toxicity and may affect the liver at repeated dose. however, more studies are needed to verify and clarify the toxic aspect of olea europea.L leaves.